1995
DOI: 10.1111/j.1464-410x.1995.tb07279.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic treatment of vesico‐ureteric reflux and urinary incontinence: technical problems in the paediatric patient

Abstract: Endoscopic treatment of VUR seems to be a valid alternative to open surgery, even though concerns remain about the long-term efficacy of collagen implantation. An important distinction should be made between early and late failure of the procedure. Early failure, which we define as persistence of reflux, is usually due to incorrect technique or technical difficulties. Late failure, or recurrence of reflux, which has previously been attributed to the biodegradability of collagen, seems to be due to the displace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(17 citation statements)
references
References 22 publications
2
13
0
2
Order By: Relevance
“…6 With glutaraldehyde cross-linked collagen, the reported success rates vary from 53% to 76%. [7][8][9][10][11][12] The largest series with the best results and the longest followup was reported by Bomalaski et al 13 They treated 40 children, including 25 with neuropathic bladder and 12 with the exstrophy-epispadias complex, with 70 glutaraldehyde cross-linked collagen injections and reported a 76% success rate (only 22% cured and 54% improved). They also reevaluated a subgroup of 7 patients after a mean followup of 4.5 years and confirmed that the cure or improvement rate remained stable with time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 With glutaraldehyde cross-linked collagen, the reported success rates vary from 53% to 76%. [7][8][9][10][11][12] The largest series with the best results and the longest followup was reported by Bomalaski et al 13 They treated 40 children, including 25 with neuropathic bladder and 12 with the exstrophy-epispadias complex, with 70 glutaraldehyde cross-linked collagen injections and reported a 76% success rate (only 22% cured and 54% improved). They also reevaluated a subgroup of 7 patients after a mean followup of 4.5 years and confirmed that the cure or improvement rate remained stable with time.…”
Section: Discussionmentioning
confidence: 99%
“…Dextranomer has been used for the treatment of vesicoureteral reflux in several hundred of children with long-term results similar to those of other bulking agents. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] The product is particularly easy to inject even through a thin needle without the need for a gun. However for endourethral injections the depth and pressure of injection are greater than those for the treatment of vesicoureteral reflux.…”
Section: Effect Of Dextranomer Based Implants On Continence and Bladdmentioning
confidence: 99%
“…Some authors distinguish between early and late failure of this procedure [13]. Early failure means persistence of reflux due to incorrect injection technique or technical difficulties, while late failure, i.e., recurrence of reflux, may be due to biodegradability of collagen or its displacement.…”
Section: Discussionmentioning
confidence: 99%
“…Frey (20,21) kollajenin tek enjeksiyonuyla 3 ay takip sonrası kür oranını 1992'deki çalışmasında %59, 1995'teki çalışmasında %63 bulmuştur. Benzer takip süresinde kür oranımız %65.6'dan fazladır ve bir aylık takip sonrası %78 kür oranı belirten Capozza ve arkadaşlarının (22) bildirdikleri oran ile karşılaştırılabir. Bir yıllık takip sonrası kür oranımız %56.2'dir.…”
Section: G Ge Er Re Eç ç V Ve E Y Yö öN Nt Te Em Munclassified
“…Bu oran Haferkamp ve arkadaşlarının (3) çalış-masında diğer yayınlardan daha düşüktür ve bu çalışmada grade1-4 reflülü toplam 57 renal ünite-ye yapılan tek kollajen enjeksiyonu sonrası 37 aylık takipte sadece 5 renal ünite (%9) reflüsüz kalmıştır. Yayınlanmış birçok çalışmada, subüreteral kollajen enjeksiyonu sonrası ilk tedavinin başarı-sızlığı ve reflü rekürrensi, tekrarlayan enjeksiyonlarla tedavi edilmiştir (21)(22)(23). Bizim çalışmamızda bir kez tekrarlanan enjeksiyonla kür oranı 12, 24, 36 aylık takiplerde sırasıyla %68.7, %53.1 ve %40.6'dır.…”
Section: G Ge Er Re Eç ç V Ve E Y Yö öN Nt Te Em Munclassified